PENERAPAN MODEL DISCOVERY LEARNING PADA PEMBELAJARAN TEMATIK UNTUK MENINGKATKAN HASIL BELAJAR SISWA - Maulana Arafat; Akhir Pauji Rambe (IAIN Padangsidimpuan, 2020)
AbstractThis study found the problem namely the low of students’ learning outcomes in grade four thematic learning SD Negeri 100101 Simatorkis. The cause was the teacher acted as a learning source and seldom to apply the model or media in process of study. So students did not understand how the concept in the learning process. This study was done to improve students’ learning results at the grade IV SD Negeri 100101 Simatorkis with apply discovery model learning. This study was classroom action research with consist of four components, they are planning, action, observation, and reflection. This study was done as long as two siclus, every sicles consist of twice meeting. Instruments for collecting the data in this study are test and observation. This study result showed that students’ learning result in the subject of thematic in every sinus grow up. In the first test, the average of students was 64,5 (30%), in the first cycles, the average of students were 67,5 (30%) become 72 (45%). In the second siclus from 75 (50%) becomes 86 (85%). The conclusion that the result of students learning grows up after the applied learning discovery model in this thematic subject at grade IV SD Negeri 100101 Simatorkis.